ANALISIS PENDAPATAN USAHATANI PADI SAWAH METODE TANAM BENIH LANGSUNG DI DESA ASTINA KECAMATAN TORUE KABUPATEN PARIGI MOUTONG - Susanta, I Wayan Erma; Antara, Made; Effendy, Effendy (AGROTEKBIS, 2016)
The aim of this research is to know the total Income and the feasibility of direct seeding method on paddy rice farming at Astina Village Torue Subdistrict Parigi Moutong Regency. This study was conducted on April to May 2015. Respondents in this research was 30 housholds chosen by following simple randing sampling method. The results showed total income was 1,346,798 IDR per hectar with average total cost 9,186,263 IDR per hectar. The direct seeding on paddy rice farming is feasible while the R/C is 2.2.Key Words : Feasibiliy, income, Paddy Rice Farming.